Microfluidic integration of photonic crystal fibers for online photochemical reaction analysis - Unterkofler, S.; Mcquitty, R. J.; Euser, T. G.; Farrer, N. J.; Sadler, P. J.; Russell, Philip St. John (Optics Letters, 2012)
Liquid-filled hollow-core photonic crystal fibers (HC-PCFs) are perfect optofluidic channels, based on their unique feature of low loss optical guidance in a liquid medium. Thereby, the overlap of the dissolved specimen and the intense light field in the micron-sized core is increased manifold as compared to conventional bioanalytical techniques, facilitating highly efficient photoactivation processes. Here we introduce a novel integrated analytical technology for photochemistry by microfluidic coupling of a HC-PCF nanoflow reactor to supplementary detection devices. Applying a continuous flow through the fiber, we deliver photochemical reaction products to a mass spectrometer in an online and hence rapid fashion, which is highly advantageous over conventional cuvette-based approaches.
EAM Import::2019-03-12